The Influence Of Financial Literacy, Self-Control, E-Wallet, And Social Media On Financial Management Of Brawijaya University Students - Michella, Agatha Kessie; T, Sutrisno (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
This study aims to analyze the influence of financial literacy, self-control, e-wallet, and social media on the financial management of accounting students of the Faculty of Economics and Business, Universitas Brawijaya. This research uses multiple regression analysis with SPSS. Sampling was conducted using a purposive sampling method. The number of respondents collected and used as research data for testing was 321 university students. The analysis shows that financial literacy, self-control, and social media have a positive influence on students' financial management. However, e-wallets did not have a significant impact on students' financial management. This study contributes to the development of the Theory of Planned Behavior by explaining how three dependent variables influence intentions in financial management and can provide practical insights to students and society for improving the quality of their financial management. Furthermore, the results of this study could serve as a foundation for universities in designing financial education programs for students.